Mass Transportation Mode Income Analysis Bus Rapid Transit Transjakarta - Alfath Satria Negara Syaban; Nurul Fitriani; Rahmat Ahmad; Putu Diva A. Sadri; Ni Luh Darmayanti (Jurnal Teknologi Transportasi dan Logistik, 2022)
Jakarta is the largest metropolitan city in Indonesia, with a current population of 10,609,681 people. The higher population in Jakarta is positively correlated with the higher demand for efficient and effective land transportation services. One of the land-transport provided by the Jakarta government is Bus Rapid Transit. The types of bus services available in Jakarta currently serve short-distance routes, with most users being middle-class workers. The problem faced by this bus service is that special lanes are often used by other road users, thus slowing down the vehicle. Bus Rapid Transit currently available is a local government service to improve the regional economy. This study uses a quantitative approach with correlation and multiple linear regression methods and analytical tools in the form of SPSS to measure the relationship between variables and ArcGIS Pro to analyze spatial data. The results obtained indicate that there are variables that affect the revenue of TransJakarta, where these variables have a simultaneous effect of 99.9% on the revenue of the TransJakarta Bus Rapid Transit. The revenue generated from this sector can be reused to improve facilities and services in the transportation sector and other related fields.